Increased BMI and Blood Lipids Are Associated With a Hypercoagulable State in the Moli-sani Cohort - de Laat-Kremers, Romy; Di Castelnuovo, Augusto; van der Vorm, Lisa; Costanzo, Simona; Ninivaggi, Marisa; Cerletti, Chiara; Huskens, Dana; De Curtis, Amalia; Gialluisi, Alessandro; Bai, Cuicui; de Gaetano, Giovanni; Yin, Dongmei; et al. (Frontiers in Cardiovascular Medicine, 2022)
The coagulation system can be assessed by the thrombin generation (TG) assay, and elevated TG is associated with an increased risk of thrombosis. Obesity had been reported to increase TG and is associated with dyslipidemia, which also predisposes to atherosclerotic cardiovascular disease (CVD). However, the effect of the blood lipid profile on TG has not been studied extensively. To gain more insight into the associations of TG, body mass index (BMI) and lipid profile, we studied TG in relation to these parameters in a large Italian population cohort, the Moli-sani study (N=22,546; age≥35; 48% men). TG was measured in plasma samples collected at the enrollment of subjects in the Moli-sani study. TG was triggered with 1 or 5 pM tissue factor, and TG parameters lag time, peak, endogenous thrombin potential (ETP), time-to-peak (TTP) and velocity index (VI). Additionally, thrombomodulin was added to assess the function of the activated protein C system during TG. In both women and men, overweight (BMI 25-30 kg/m2) and obesity (BMI>30 kg/m2) were significantly associated with higher ETP, peak and VI (all p<0.001). High total cholesterol, triglycerides and LDL-cholesterol levels were significantly associated with increased ETP and peak (all p<0.001). Linear regression analysis revealed that the ETP is positively associated with both plasma LDL and HDL cholesterol levels, whereas the velocity index is positively associated with HDL cholesterol. Additionally, ETP, peak and VI a significantly associated with the plasma triglycerides content. In conclusion, our study shows significant associations of high BMI and blood lipid levels with increased TG parameters, and this hypercoagulability may partly explain the increased risk of CVD in individuals with obesity and/or dyslipidemia.